An Econometric Analysis of the Peninsular Malaysia Beef Market - Sukir, Sarmin (1998)
The beef industry is one of the most important industries for supplying animal protein after fish and chicken. Various studies have been conducted to improve the local contribution to the industry. But the local beef industry performance is slowing down resulting in an increasing amount of beef being imported from other countries. In this study, an econometric model has been developed, analysed and validated to satisfy the objectives of determining and analysing the important factors and their linkages relating to beef animal development, the supply of beef animals for slaughter, and the demand for beef. The equations are estimated individually by the respective ordinary or two stage least square methods, and the whole model is solved by using a microcomputer TSP Programme. The results of the study indicate that, for beef cattle, the previous number of females less than 3 years old and males more than 3 years old are two important animal components that determine the number of beef animals. For dairy cattle, the current and previous number of male and female dairy cattle more than 3 years old and the previous female dairy cattle less than 3 years old are the important components determining the dairy cattle number. And for the buffalo, the previous number of females more than 3 years old is the most important determinant for buffalo number. Beef prices, import of animals and the existence of Maju ternak have a positive effect on the beef animals number, while the slaughtering of animals and disease outbreak have a negative effect. The previous number of female beef cattle less than 3 years old is the most important determinant for cattle to be slaughter. For buffalo, both the current number of males and females more than 3 years old are the important determinants. The total population and the prices of beef are the important determinants for beef demand in Peninsular Malaysia. Most of the dependent variables in the equations are explained by the explainatory variables at more than a 95% level. The estimated coefficients of the explainatory variables conform to the expected prior signs, and most of them are statistically significant. The simulated values obtained closely follow the actual values. From this analysis, therefore, the econometric model formed is able to represent the Peninsular Malaysia beef market and can be used for policy analysis and other studies.